Materi Muatan Peraturan Perundang-Undangan UU 1945 - Mimi Atika Rahma; Ahmad Fauzy; Dini Febrianti Br Sinaga; Krisman Adam Simamora (Fakultas Syariah IAIN Laa Roiba Bogor, 2024)
The period between 2004 and 2009 saw a lot of work from the office in charge of making laws (the Position Establishment Act) which produced a number of non-partisan laws for the general public. Therefore, it is detrimental to the community because it is not in line with what is generally agreed upon by the community, as stated in the Basic Regulations (1945 Constitution), which are the source and basis for the formulation of the law in question. As a result, the Constitutional Court has conducted many judicial reviews based on citizen requests. In this regard, the authors conducted a normative review and concluded that certain laws conflicted with the Uniform Unified Development Act of 1945. The Prolegnas list compiled by the DPR and the President did not always use clear, precise and consistent criteria for laws. This means that several laws enacted in the DPR for the 2004–2009 period did not meet the standards for good lawmaking set forth in Law Number 12 of 2011 concerning Establishment of Accounting Principles. Keywords: Regulations, Legislation, material.